The Influence of Multinationality on Determinants of Change in Debt Level: Empirical Evidence from Indonesia - Utama, Cynthia A.; Rahmawati, Santi (Gadjah Mada International Journal of Business, 2010)
This study aims to investigate whether: (1) the change in debt level is affected by agency problems, the probability of bankruptcy, firm size, and profitability; (2) the change in debt level is affected by multinationality (i.e., multinational corporations (MNCs) or domestic corporations (DCs)) and whether multinationality affects the relationship of agency problems, probability of bankruptcy, size, and profitability to the change in debt level. This study finds that in general, the change in debt level is negatively affected by the probability of bankruptcy and size. Furthermore, the changes in debt level for Indonesian MNCs are negatively affected by the probability of bankruptcy, firm size, and profitability. The negative effects of size and profitability on the change in debt level support the view of the Pecking Order Theory. However, for domestic companies, none of the determinants has a significant effect on the change in debt level. We also find that: (1) only size has a negative influence on the change in debt level when we include all interactive terms in the model; (2) if we include one interactive variable at a time, the probability of bankruptcy, firm size, and profitability have negative influences on the change in debt level; in addition, a positive impact of agency problems on the change in debt level is more pronounced for MNCs compared to DCs. Overall, we conclude that multinationality affects the relationship between agency problems and the change in debt level.Keywords: capital structure; Indonesia leverage; multinational corporations